Simulation of flow behaviour of open channel flow through a linear straight contraction using computational approach / Muhammad Amir Ashraf Mohd Haziman - Mohd Haziman, Muhammad Amir Ashraf (2022)
This project investigates open channel flow behaviour through the linear straight contraction. On the test portion, several angles of wall gaps are installed. This will result in a varied water flow for each wall gap. This method we can use in the weirs to slow down the flow of water so that we can minimize the velocity of movement for the fluid. A weir is a small dam that spans a body of water like a river and can control flood problems. This objective is to determine the shape and velocity of the water flow. The application used in this experiment are CAD and CFD software. The material of the test section is made from transparent acrylic cover. The expected result is that a larger wall gap will reduce water flow velocity. The angle of the wall gap will influence the water flow rate. The larger the angle used, the water flow rate will decrease. At the same time, the resulting water patterns may also be different. In conclusion, what is the relationship between the wall gap angle and the resulting water flow velocity?